A German Employee Network and Union Renewal: The Siemenskonflikt - Croucher, Richard; Martens, Helmut; Singe, Ingo (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2007)
The paper shows how redundancies were resisted by Hi-Tech workers in a large German company. It details an employee network’s emergence to provide support to individuals and to pursue legal cases against the company, and analyzes the network’s norms and operation. The network operated in complementary ways to the union and works council, to achieve a favourable outcome. The case is used to test theoretical propositions derived from literature on Hi-Tech workers, union renewal and mobilization theory and it is suggested that mobilization theory requires further extension in several directions.